Short Communication: Floral diversity of honey bee-collected pollen (Apis cerana) colonies in the Ir. H. Djuanda Forest Park, West Java, Indonesia - Syayidah Nuriyah; Teguh Husodo; Wawan Hermawan; ARIEF ANSHORY YUSUF; Hikmat Kasmara; Joko Kusmoro; Indri Wulandari; Sya Sya Shanida (Nusantara Bioscience, 2021)
Abstract. Nuriyah S, Husodo T, Hermawan W, Yusuf AA, Kasmara H, Kusmoro J, Wulandari I, Shanida SS. 2021. Short Communication: Floral diversity of honey bee-collected pollen (Apis cerana) colonies in the Ir. H. Djuanda Forest Park, West Jawa, Indonesia. Nusantara Bioscience 13: 185-193. Honey bees, especially Apis cerana Fabr., need feed sources from nectar and pollen. In addition, pollen is essential for sexual reproduction. However, various plants in the forest park have not been supported by information on pollinated plants or as feed sources by A. cerana. Therefore, this study should be conducted as essential information to reveal the pollens as feed sources of A. cerana in the Ir. H. Djuanda Forest Park, West Java. However, there is little information about those plants in the forest park, West Java. Therefore, this study aimed to reveal the pollens as feed sources of A. cerana in the Ir. H. Djuanda Forest Park. Sampling was collected on 45 honey bee-collected pollen from three cultivation areas. Pollen preparation was carried out using the acetolysis method. Based on the study results, 70 species of pollen flora of 36 families were found in Ir. H. Djuanda Forest Park vegetation in the A. cerana. However, further study is needed regarding the frequently visited plants used as feed sources or pollinating by A. cerana. In addition, considering that the honey bees cultivated in the forest park are dominated by A. cerana, further studies are needed on regularly pollinated plants to maximize the yield of honey cultivation.